Increased CDKL3 expression predicts poor prognosis and enhances malignant phenotypes in esophageal squamous cell carcinoma. Issue 5 (1st November 2018) - Ye, Wenguang; Zhu, Jian; He, Dongjie; Yu, Dequan; Yang, Haihua; Wang, Wei; Zhang, Mingxin; Zhou, Suna
Abstract: Background: Cyclin‐dependent kinase‐like 3 (CDKL3) is a putative protein serine kinase and plays an important role in the regulation of cell growth and/or differentiation. However, studies on the function of CDKL3 in esophageal squamous cell carcinoma (ESCC) is limited. In our study, we explored the role and prognosis of CDKL3 in ESCC and underlying mechanism. Materials and methods: The expression of CDKL3 was investigated by quantitative reverse transcription polymerase chain reaction and immunohistochemical staining. CDKL3 expression was downregulated by the RNAi‐mediated knockdown. The functions of CDKL3 on cell growth were assessed by Celigo image cytometry, MTT assay, cell‐cycle analysis, Annexin V assay, and caspase‐3/7 activity analysis. The effect of CDKL3 on cellular invasive was investigated by the Transwell assay. Pathscan Stress Signaling Antibody Array was used to study the underlying mechanism. Additionally, the association between the survival and CDKL3 expression in ESCC were evaluated based on the TCGA data. Results: CDKL3 was highly expressed in ESCC tissues and cell lines. TE‐1 cells transfected with CDKL3‐shRNA‐lentivirus significantly decreased CDKL3 expression and resulted in inhibiting cell proliferation, inducing the S‐phase cell‐cycle arrest, attenuating cellular invasive and increasing cell apoptosis. The expression of pERK1/2, p‐Akt, p‐Smad2, p‐p38 mitogen‐activated protein kinase, cleaved caspase‐7, and phospho‐Chk1 were significantly decreased by CDKL3 knockdown. In addition, high expression of CDKL3 was associated with shorter overall survival. Conclusion: Our findings suggest that higher expression of CDKL3 is correlated with poor prognosis in patients with ESCC and play a vital role in the malignant phenotype of ESCC cell lines, which indicating that CDKL3 may be as a new therapeutic target in ESCC. Abstract : To our knowledge, this is the first reports on the expression, prognostic value and function of CDKL3 in esophageal squamous cell carcinoma (ESCC). Through comprehensive analysis, we show that CDKL3 may act as an oncogene in ESCC and CDKL3 might be a potential biomarker in the diagnosis and a therapeutic target in treatment of patients with ESCC.